2013
DOI: 10.1158/1078-0432.ccr-12-2799
|View full text |Cite
|
Sign up to set email alerts
|

PLK1 Inhibitors Synergistically Potentiate HDAC Inhibitor Lethality in Imatinib Mesylate–Sensitive or –Resistant BCR/ABL+ Leukemia Cells In Vitro and In Vivo

Abstract: Purpose To determine whether PLK1 inhibitors (e.g. BI2536) and HDAC inhibitor (e.g. vorinostat) interact synergistically in CML cells sensitive or resistant to imatinib mesylate (IM) in vitro and in vivo. Experimental Design K562 and LAMA84 cells sensitive or resistant to IM and primary CML cells were exposed to BI2536 and vorinostat. Effects on cell viability and signaling pathways were determined using flow cytometry, western blotting, and gene transfection. K562 and BV173/E255K animal models were used to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 49 publications
2
19
0
Order By: Relevance
“…Previous reports with BI 2536 have shown that inhibition of PLK1 in vitro also boosts the antineoplastic effects of other chemotherapeutics, such as temozolomide (TMZ) [30], MTX and CDDP [31], DXR and cyclophosphamide [32], docetaxel [33], and histone deacetylase inhibitors [34], among others. It is well recognized that treatment efficacy (irrespective of the tumor type) is often achieved by combining agents with diverse mechanisms of action and different spectra of toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports with BI 2536 have shown that inhibition of PLK1 in vitro also boosts the antineoplastic effects of other chemotherapeutics, such as temozolomide (TMZ) [30], MTX and CDDP [31], DXR and cyclophosphamide [32], docetaxel [33], and histone deacetylase inhibitors [34], among others. It is well recognized that treatment efficacy (irrespective of the tumor type) is often achieved by combining agents with diverse mechanisms of action and different spectra of toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…S. Liu, Song, & Liu, 2010). Co-treatment of imatinib-sensitive and –resistant Bcr-Abl + cells with the PLK-1 inhibitor BI2536 and vorinostat synergistically induced cell death with minimal toxicity towards normal cells (Dasmahapatra, Patel, Nguyen, Attkisson, & Grant, 2013). The combination triggered pronounced mitochondrial dysfunction, inhibition of phospho-BCR/ABL, caspase activation, PARP (poly ADP ribose polymerase) cleavage, ROS generation and DNA damage, and was dramatically effective in a xenograft model of Bcr-Abl + leukemia (Dasmahapatra et al, 2013).…”
Section: Rational Combinations Involving Hdacis and Other Novel Tmentioning
confidence: 99%
“…Co-treatment of imatinib-sensitive and –resistant Bcr-Abl + cells with the PLK-1 inhibitor BI2536 and vorinostat synergistically induced cell death with minimal toxicity towards normal cells (Dasmahapatra, Patel, Nguyen, Attkisson, & Grant, 2013). The combination triggered pronounced mitochondrial dysfunction, inhibition of phospho-BCR/ABL, caspase activation, PARP (poly ADP ribose polymerase) cleavage, ROS generation and DNA damage, and was dramatically effective in a xenograft model of Bcr-Abl + leukemia (Dasmahapatra et al, 2013). Although Bcr-Abl signals downstream to PLK-1 (Gleixner et al, 2010), enhanced Bcr-Abl pathway inhibition was not felt to be the sole mechanism for lethality of the BI2536/vorinostat regimen; rather, potentiation of DNA damage and disabling of the DDR appeared to predominate (Dasmahapatra et al, 2013).…”
Section: Rational Combinations Involving Hdacis and Other Novel Tmentioning
confidence: 99%
See 1 more Smart Citation
“…The pan-HDACIs suberoylanilide hydroxamic acid 96 and LAQ824 97 down-regulated BCR-ABL1 levels and induced apoptosis in CML-mBC cells, whereas HDACIs potentiated the activity of ABL1 TKIs 98 and inhibitors of polo-like kinase 1 99 against resistant CML cells in vitro and in vivo. More relevant to targeting CML stem cells, a recent study showed that LBH589 (panobinostat) induced apoptosis in quiescent CML progenitors that are resistant to elimination by imatinib and reduced NSG engraftment by these cells.…”
Section: Targeting Signaling Pathways Implicated In CML Stem Cell Surmentioning
confidence: 99%